Coordinated enactment: how organizational departments work together to implement CSR - Risi, David (2022)
Research on the implementation of corporate social responsibility (CSR) has revealed the critical role of CSR departments vis-a-vis functional departments. While both CSR and functional departments influence CSR implementation, the question of how they work together remains underexamined. We address this question by mobilizing and merging two complementary yet separate perspectives on CSR implementation: "coordination" and "enactment." Building on a comparative case study involving seven large Swiss financial institutions that have established CSR departments and implemented CSR to varying extents, we inductively derive six courses of actions conducing to CSR implementation, involving both coordination and enactment. We distinguish between four courses of actions in the CSR departments (centralizing, coalescing, orchestrating, and consulting) and two courses of actions in the functional departments (decentralizing and tailoring). As our data suggest that coordination and enactment work in tandem, we capture these insights in a model of CSR implementation as coordinated enactment. Our research contributes to the literature by explaining how CSR departments and functional departments enact and simultaneously coordinate CSR at a particular implementation stage, thus illuminating how and why the variance in CSR implementation occurs.